Avaliação e caracterização do comportamento geomecânico de agregados oriundos de jazidas da região sudeste do Rio Grande do Sul e Santa Catarina - Ceccato, Haline Dugolin (2021)
The evaluation and characterization of mineral aggregate is extremely important in the paving scenario, considering that more than 80% of the volume of asphalt mixtures is composed of this type of material. Thus, its acceptance in construction is mainly conditioned by its technological characteristics. In recent years, several studies have been performed with this purpose, however, with little or no information about plutonic and metamorphic rocks. So, this study aims to contribute to the technological characterization of plutonic and metamorphic rocks, aiming its application in diverse civil construction purposes, in addition to add to the national database by means of the study of different rock materials from quarries located in the states of Santa Catarina and Rio Grande do Sul. For this purpose, a range of laboratory tests were performed, including: petrographic analysis, physical indices, mechanical strength, aggregate morphology and adhesion to the asphalt binder. Based on the presented results, the field step proved to be essential for the knowledge and understanding of the characteristics and behaviour of the different aggregates. 12.5 mm, 9.5 mm and 4.75 mm diameter aggregate of mafic granulite, felsic granulite, biotite gneiss, syenogranite and monzogranite porphyry were investigated. The results showed that the rock granulation as well as the mineralogy presents a direct correlation with the mechanical strength of the material evaluated by the Los Angeles Abrasion, Treton and Crushing tests. Thus, aggregates whose origin comes from coarse-grained rocks tend to show higher mass loss and, consequently, less degradation strength. However, for the Point Load test, the mineralogy and alteration degree of irregular samples are factors that influence the strength degree of the rock. Shape evaluation tests were carried out, both through laboratory procedures and through digital image processing (DIP). Although the DIP test is more functional and seeks greater accuracy, the results showed that, even so, it should be used with caution, especially in the evaluation of angularity and rock texture. Likewise, the conventional fine aggregate angularity test (FAA) seems to be not satisfactory for assessing the angularity of fine aggregate for paving purposes, and this conclusion is also supported by other authors. In addition, the five studied deposits show poor adhesion to the conventional asphalt binder, which makes its use in asphalt mixtures unfeasible, requiring the use of dope. The results of the tests were analysed towards other pre-existing ones, creating an extensive database with deposits in Rio Grande do Sul, Santa Catarina, São Paulo, Mato Grosso and Rio de Janeiro, in order to facilitate access to the characteristics of the crushed material. from different lithologies. Finally, a statistical study was developed to increase the reliability of the obtained results.